2019
DOI: 10.1002/jcsm.12461
|View full text |Cite
|
Sign up to set email alerts
|

The systemic activin response to pancreatic cancer: implications for effective cancer cachexia therapy

Abstract: BackgroundPancreatic ductal adenocarcinoma (PDAC) is a particularly lethal malignancy partly due to frequent, severe cachexia. Serum activin correlates with cachexia and mortality, while exogenous activin causes cachexia in mice.MethodsIsoform‐specific activin expression and activities were queried in human and murine tumours and PDAC models. Activin inhibition was by administration of soluble activin type IIB receptor (ACVR2B/Fc) and by use of skeletal muscle specific dominant negative ACVR2B expressing trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 66 publications
3
72
0
Order By: Relevance
“…Moreover, as TGF-β members such as activin A, activin B, growth differentiation factor-11, and myostatin have been associated with or shown to induce skeletal muscle wasting in cancer and non-cancer settings, targeting of the ACVR2B receptor has become a promising therapeutic approach in combating cachexia. [14][15][16][17][18][19][20][21] In line with this notion, using ACVR2B/Fc, a soluble ACVR2B synthetic peptide inhibitor, our group and others have demonstrated preservation of skeletal muscle in experimental models of lung and CRC cachexia, as well as following chronic administration of several anticancer drugs. 17,[22][23][24] Moreover, targeting ACVR2B signalling has shown to preserve fat and bone mass and mildly preserve cardiac size in experimental models of cancer-induced and chemotherapy-induced muscle wasting.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, as TGF-β members such as activin A, activin B, growth differentiation factor-11, and myostatin have been associated with or shown to induce skeletal muscle wasting in cancer and non-cancer settings, targeting of the ACVR2B receptor has become a promising therapeutic approach in combating cachexia. [14][15][16][17][18][19][20][21] In line with this notion, using ACVR2B/Fc, a soluble ACVR2B synthetic peptide inhibitor, our group and others have demonstrated preservation of skeletal muscle in experimental models of lung and CRC cachexia, as well as following chronic administration of several anticancer drugs. 17,[22][23][24] Moreover, targeting ACVR2B signalling has shown to preserve fat and bone mass and mildly preserve cardiac size in experimental models of cancer-induced and chemotherapy-induced muscle wasting.…”
Section: Introductionmentioning
confidence: 93%
“…These ligands initiate their effects by binding to the activin receptor type 2B (ACVR2B). It was recently shown in a murine orthotopic model of pancreatic ductal adenocarcinoma that the tumors both express activins and induce expression in distant organs, leading to elevated levels of circulating activin [13]. Blockage of the ACVR2B receptor has therefore become a therapeutic target for the treatment of cachexia.…”
Section: Introductionmentioning
confidence: 99%
“…Our studies have shown that tumor-derived Activin A acts on the muscle to upregulate the expression of Twist1, which in turn induces the synthesis of the muscle-specific ubiquitin ligases, MuRF1 and Atrogin1, thereby causing muscle cachexia by facilitating muscle protein degradation (Figure 1; Parajuli et al, 2018). In experimental studies, serum activin levels correlated with PDAC-induced cachexia and eventual mortality (Zhong et al, 2019). In the murine model of PDAC-induced cachexia, activins (activin-βA, or Inhba) are expressed, both in tumor cells and tumor stromal cells.…”
Section: Therapeutic Potential Of Twist1 In Cancermentioning
confidence: 76%
“…Tumor-derived Activin A acts on the muscle to upregulate the expression of Twist1, which in turn induces the synthesis of the muscle-specific ubiquitin ligases (MuRF1 and Atrogin1), thereby causing cancer cachexia by facilitating muscle protein degradation (Parajuli et al, 2018). and cachexia with the resultant effect being prolonged survival (Zhong et al, 2019). Moreover, using the pharmacological drug JQ1, a small molecule that suppresses Twist1 activity by blunting its binding to MuRF1 and Atrogin1 promoters, muscle cachexia could be reversed in PDAC mice deleted of Twist1, indicating that inhibition of Twist1 activity in muscle in indispensable for preventing muscle cachexia.…”
Section: Therapeutic Potential Of Twist1 In Cancermentioning
confidence: 99%